Evaluation of the Effects of Low-Level Laser Therapy on Diabetic Bone Healing - DİKER, Nurettin; DİKER, NURETTİN; Aytac, Duygu; Helvacioglu, Fatma; Dagdelen, Cansu; Oguz, Yener (My University, 2019)
The aim of the present study was to evaluate the effects of low-level laser therapy (LLLT) and biphasic alloplastic bone graft material on diabetic bone healing. Induction of diabetes was performed in 14 male Sprague-Dawley rats by intraperitoneal injection of a 50 mg/kg dose of streptozotocin. Two bilaterally symmetrical non-critical-sized bone defects were created in the parietal bones in each rat. Right defects were filled with biphasic alloplastic bone graft. Rats were randomly divided into 2 groups, with 1 group receiving 10 sessions of LLLT (GaAlAs, 78.5 J/cm(2), 100mW, 0.028 cm(2) beam). The LLLT was started immediately after surgery and once every 3 days during postoperative period. At the end of treatment period, new bone formation and osteoblast density were determined using histomorphometry. Empty (control), graftfilled, LLLT-treated and both graft-filled and LLLT-treated bone defects were compared. New bone formation was higher in the graft treatment samples compared with the control (P = 0.009) and laser samples (P = 0.029). In addition, graft-laser combination treatment samples revealed higher bone formation than control (P = 0.008) and laser (P = 0.026) samples. Osteoblast density was significantly higher in the laser treatment (P < 0.001), graft treatment (P = 0.001) and graft-laser combination treatment (P < 0.001) samples than control samples. In addition, significantly higher osteoblast density was observed in the graft-laser combination treatment samples compared to the graft treatment samples (P = 0.005). The LLLT was effective to stimulate osteoblastogenesis but failed to increase bone formation. Graft augmentation for treatment of bone defects seems essential for proper bone healing in diabetes, regeneration may be supported by the LLLT to enhance osteoblastogenesis.